Po sledeh Antona Martina Slomška v Občini Brežice (University of Maribor Press, 2021)
Following the Trails of Anton Martin Slomšek in the Municipality of Brežice. Anton Martin Slomšek took up a post of the priest in Bizeljsko, at the Church of Saint Lawrence. With his activities he was influential even abroad, for instance in Croatia, where he was well-known for being an excellent educator as well as a spiritual and a literary leader. As a part of this project we summarized his works and invented two different products for tourists, namely: the short movie and the poster, within which we created a totally new path for the tourists, interested in this kind of cultural heritage. The route takes us from the birthplace of the beatified Anton Martin Slomšek to the region of Posavje and ends in the previous primary school in Brežice, today known as the Slomšek’s Home. The path is shown in the short movie and in the poster.